Biomechanical Evaluation of Fingers Repetitive Voluntary Tasks in Chronic Stroke Survivors - Muhammad Adeel; Chih-Wei Peng; I-Jung Lee; Bor-Shing Lin (IEEE Access)
A chronic stroke affects hand mobility limiting the normal functioning of the finger joints. The voluntary tasks with a repetitive motion can identify the limitation in the range of motion (ROM) to enhance the hand functioning of stroke survivors. Therefore, we compared two voluntary tasks fast ball squeezing (FBS) and slow ball squeezing (SBS), and analyzed the variability of these tasks for finger pressure and ROM in chronic stroke survivors. An experimental study with 22 healthy and 39 chronic stroke participants was conducted. All of them wore an upper limb motion capture device (UMCD) to record the active (AROM) of finger joints during FBS and SBS tasks for 20 repetitions. The data were analyzed into the joint angle and pressure to compare these tasks and their variability. While comparing the FBS and SBS tasks, left-side pressure and both sides’ ROM attained the level of significance ( $p < 0.05$ ) except for right-side pressure in healthy controls. However, for stroke participants, right-side pressure and left-side ROM differed significantly. The finger pressure and ROM for the right vs. left side are changed significantly for both tasks in healthy control and stroke survivors except for SBS pressure in the stroke group ( $p$ = 0.119). The right FBS and SBS are more sensitive to changes in finger pressure and left SBS for ROM in healthy control while in stroke survivors, left FBS and SBS pressure and ROM are sensitive. The variability for pressure is higher and easy to detect as compared to ROM.